Cycloaddition Reactions of an Active Cyclic Phosphane/Borane Pair with Alkenes, Alkynes, and Carbon Dioxide. Issue 6 (21st January 2020) - Jie, Xiaoming; Sun, Qiu; Daniliuc, Constantin G.; Knitsch, Robert; Hansen, Michael Ryan; Eckert, Hellmut; Kehr, Gerald; Erker, Gerhard
Abstract: The active six‐membered cyclo‐FLP 6 undergoes a rapid P/B addition reaction to carbon dioxide. At elevated temperature, the resulting heterobicyclo[2.2.2]octane derived product 7 undergoes ring opening and equilibrates with the cyclotetramer (7)4 . In the large macrocyclic structure, four monomeric six‐membered cyclo‐FLP units are connected by four CO2 molecules to form the supramolecular ring system. The P/B cyclo‐FLP 6 undergoes a variety of additional cycloaddition reactions. Abstract : Six‐membered cyclic frustrated phosphane/borane Lewis pair adds carbon dioxide under mild conditions. Crystallization gave the unique macrocyclic tetramer with bridging CO2 between the individual cyclo‐FLP units (see scheme).